Seven Jump PBL to Connect Modern Problems to Sciences - Harimurti, Shubhi Mahmashony (Asia Pacific Journal of Management and Education (APJME), 2023)
Contemporary problems are often visible only from one facet, even though there are many components that could become the solution to the issues. The sphere of sciences which are to be had in several universities can also be correlated with the current issues through their views. This research aimed to facilitate and assist college students in relating modern problems to their discipline of sciences. This research offered Seven Jump Problem-Based Learning (PBL). The model is performed via an academic in which students are divided into small groups and facilitated through an instructor. This research used class action research and qualitative and quantitative technique. The result of this research is the students can correlate contemporary problems to their fields.